Penurunan Kualitas Savana Bekol sebagai Feeding Ground bagi Rusa (Cervus timorensis) dan Banteng (Bos javanicus) di Taman Nasional Baluran Jawa Timur - Djufri Djufri (Universitas Syiah Kuala, 2009)
This research aim to know : (1). species of grass eaten by deer and species of grass predominating area of savannah Bekol. (2). Species eaten by bull, and (3). Factors causing downhill it quality of savannah Bekol. Method used for inventories of species eaten by deer and bull is method of transek combined with method square. While to collect data of factors causing downhill it quality of savannah of Bekol with direct perception in field and muster relevant information from data sekunder. The conclusion from this research is (1). Found 12 species of grass eaten by deer, and 3 species among others as dominant species that is bayapan (Brachiaria reptans), red lamuran (Dichantium coricosum), and tuton (Dactyloctenium aegyptium). (2). found 50 species as food of bull in savannah Bekol from 60 of species of compiler savannah of this area. (3). Factors influencing reduction of quality of savannah in Bekol is : Invasion A. nilotia, bush groaning savannah, existence of tread by animal, fire effect, and over grazing.